1995
DOI: 10.1016/0029-7844(95)00275-v
|View full text |Cite
|
Sign up to set email alerts
|

Implications of idiopathic preterm delivery for previous and subsequent pregnancies

Abstract: Idiopathic preterm birth is associated with emergency cesarean delivery at term in previous pregnancies and infants with lower birth weight in previous and subsequent pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 13 publications
2
43
1
2
Order By: Relevance
“…Epidemiological studies have clearly demonstrated that a prior history of PTD is a major risk factor for its recurrence in a subsequent pregnancy 66,67 . It has been suggested that several candidate genes for polymorphisms associated with labor exist 68 .…”
Section: Genetic Factors and Preterm Deliverymentioning
confidence: 99%
“…Epidemiological studies have clearly demonstrated that a prior history of PTD is a major risk factor for its recurrence in a subsequent pregnancy 66,67 . It has been suggested that several candidate genes for polymorphisms associated with labor exist 68 .…”
Section: Genetic Factors and Preterm Deliverymentioning
confidence: 99%
“…Although many risk scoring systems have been devised, predicting a preterm birth is difficult. Prior preterm birth is a strong predictor of preterm delivery [2]. Although the pathogenesis of preterm labor is not well understood, progesterone withdrawal is theorized to play a part [3].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for preterm delivery were: a history of preterm delivery, smoking during pregnancy, and a history of abortion. Kristensen et al [9] found that a previous spontaneous preterm delivery gives a fivefold risk increase in preterm birth in the next pregnancy compared with women with first term delivery. Adams et al [10] found in a population-based cohort among almost 123,000 white and 56,000 black women that there is a high association between a preterm delivery in the first pregnancy and recurrence in the next one.…”
Section: Risk Factors For Recurrent Preterm Birthmentioning
confidence: 98%
“…Several studies have shown that there is an increased risk of preterm delivery when the first delivery was preterm [9][10][11]. An early prior spontaneous preterm birth is more predictive of recurrence and is highly associated with subsequent early spontaneous preterm birth [12].…”
Section: Introductionmentioning
confidence: 99%